Evaluation of bleeding and anticoagulation markers by edoxaban and low‐dose cyclosporine: A case series study. (18th October 2022) - Hirai, Toshinori; Shinogi, Yuri; Ikejiri, Makoto; Murata, Tomohiro; Iwamoto, Takuya
Abstract: It was reported that high‐dose cyclosporine at 500 mg daily increases edoxaban exposure. We investigated whether cyclosporine <500 mg daily leads to edoxaban‐induced bleeding in the clinical setting. This case series study included patients receiving edoxaban and cyclosporine at Mie University Hospital. The outcomes were bleeding and anticoagulant markers, including activated partial thromboplastin time (APTT), prothrombin time (PT), and the international normalized ratio of prothrombin time (PT‐INR). We examined the genotypes of cytochrome P450 3A5 ( CYP3A5 ), multidrug resistance 1 ( ABCB1 ), and solute carrier organic anion transporter 1B1 ( SLCO1B1 ). Trends in anticoagulant markers were analyzed. Thirteen patients received edoxaban (standard dose; n = 3 and reduced dose; n = 10) and cyclosporine (1.94 ± 1.42 mg/kg). A bleeding event occurred in one patient receiving a standard dose of edoxaban plus cyclosporine of 25 mg daily (HAS‐BLED score of 2 and genotypes; CYP3A5*3/*3, ABCB1 3435CT, and SLCO1B1*1a/*1b ). After edoxaban treatment, anticoagulant markers were prolonged (APTT; 27.95 ± 3.64 s vs. 31.11 ± 3.90 s, p < 0.001, PT; 11.53 ± 1.01 s vs. 13.03 ± 0.98 s, p = 0.002, PT‐INR; 0.98 ± 0.09 vs. 1.11 ± 0.11, p = 0.007). In summary, the genotypes of CYP3A5, ABCB1, and SLCO1B1 and the dosage of edoxaban may affect the risk of bleeding by edoxaban when co‐administered with cyclosporine, even at low doses. Abstract : Low‐dose cyclosporine may increase the risk of bleeding even when administered with edoxaban at a standard dose. Edoxaban prolonged anticoagulation markers, APTT, PT, and PT‐INR, in patients treated with cyclosporine. Genotypes of CYP3A5, ABCB1, and SLCO1B1 may influence the interaction between edoxaban and cyclosporine.